Novel Synthesis of 3-(Substituted phenyl)-2-[(substituted benzoyl)imino]-1,3-thiazolidine-4-one Derivatives from Substituted Thiourea - Pourshamsian, Kh.; Montazeri, N.; Banihashemi, S.M.; Razikazeni, S. (Asian Journal of Chemistry, 2012)
In this work, we proposed the synthesis of several new derivatives of 3-(substituted phenyl)-2-[(substituted benzoyl)imino]-1,3-thiazolidine-4-one by using substituted thiourea and chloroacetic acid. The structure of compounds were confirmed with IR, 1H NMR and 13C NMR spectroscopy.